PENGARUH PENERAPAN KODE ETIK UMKM TERHADAP KINERJA UMKM DI SURAKARTA DENGAN PERAN KOMITMEN MANAJEMEN SEBAGAI VARIABEL MODERASI DAN KAPABILITAS SUMBER DAYA SEBAGAI VARIABEL MEDIASI - Bakar Akbar, Abu; Yuniawan, Ryan; Lubis, Arowadi (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the effect of implementing a code of ethics for MSMEs on the performance of MSMEs in Surakarta. In addition to the direct effect, the study also examines the role of management commitment as a moderating variable and resource capability as a mediating variable. The research approach is quantitative with a survey method using a questionnaire and analyzed through PLS SEM. The research sample was 140 MSMEs in Surakarta that met certain criteria. The results showed that the implementation of a code of ethics had a positive and significant effect on MSME performance (β = 0.46, p < 0.01). Management commitment was shown to moderate the relationship between code of ethics → performance (interaction coefficient = 0.18, p < 0.05). Resource capability was also shown to partially mediate the effect between the code of ethics and performance (indirect effect = 0.15, significant). These findings indicate that a code of ethics is not merely a normative instrument, but must be implemented with managerial support and increased internal capabilities to have a positive impact on performance.